Negara samseng membuka topeng Amerika - Blum, William (Institut Terjemahan Negara Malaysia Berhad, 2007)
Learn about decades of ubiquitous U.S. cruelty, kept-remarkably-from penetrating or shocking world conscience. Though President Clinton calls America "the world's greatest force for peace, " Blum shows that our rogue state is really a marauding Western brute